2022
DOI: 10.7150/thno.73226
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ASGR2 by microplastic exposure leads to resistance to therapy in gastric cancer

Abstract: Background: Microplastics (MPs) are a new global environmental threat. Previously, we showed the biodistribution of MPs using [ 64 Cu] polystyrene (PS) and PET in mice. Here, we aimed to identify whether PS exposure has malignant effects on the stomach and induces resistance to therapy. Methods: BALB/c nude mice were fed 1.72 × 10 4 particles/mL of MP. We investigated PS accumulation in the stomach using radioisotope-labeled and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Two of the in vivo discussed studies reported that MNPLs were administered in drinking water or food although no specification on the consumption per animal was given [41,42]. Similarly, Kim and colleagues reported the concentration of particles administered per mouse without mentioning the volume administered [35]. A comprehensive and detailed description of these procedures is fundamental for comparing the results between studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of the in vivo discussed studies reported that MNPLs were administered in drinking water or food although no specification on the consumption per animal was given [41,42]. Similarly, Kim and colleagues reported the concentration of particles administered per mouse without mentioning the volume administered [35]. A comprehensive and detailed description of these procedures is fundamental for comparing the results between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, and as indicators of an advanced tumoral phenotype, there was a significantly elevated number of colonies able to grow in soft-agar and increased cell migration capacity, as well as an aggressive tumoral phenotype, namely, increased invasion capacity, changes in pluripotency markers (upregulated Klf4, Nanog, Notch2, and Oct3/4 and downregulated Sox2) and formation of tumorspheres due to the treatment of the cells with PSNPLs for 24 weeks. On the other hand, Kim and colleagues studied carcinogenicity-related endpoints in AGS, MKN1, MKN45, NCI-N87, and KATO III human gastric cancer cell lines after the exposure to 8.61 × 10 5 particles/mL of PSMPLs (9.5-11.5 µm) for 4 weeks [35]. As a result of the exposure, all cell lines increased their proliferation and migration rates, and most of them except NCI-N87 cells underwent invasion induction.…”
Section: In Vitro Studies On Carcinogenicity-related Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several research works have explored the effects of plastic on humans, its impact on the stomach is still unclear (Campanale et al 2020 ). Recently, Kim et al ( 2022 ) demonstrated that long-term exposure to microplastics can increase the risk of stomach cancer. The presence of microplastics has caused the enhanced expression level of asialoglycoprotein receptor 2 (ASGR2).…”
Section: Detrimental Effects Of Microplastics Ingestion On Human Healthmentioning
confidence: 99%
“…The elevated level of ASGR2 indicates the presence of typical cancer hallmarks such as CD44, N-cadherin, programmed death ligand 1 and proliferation. In addition, the excess exposure to microplastics caused a decrease in survival rate and an increase in the growth of tumours (Kim et al 2022). Wang et al (2020c) reported that the different size of microplastics affects their toxicity in humans.…”
Section: Microplastic-induced Cancermentioning
confidence: 99%